2019
DOI: 10.1016/j.joca.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated post traumatic osteoarthritis in a dual injury murine model

Abstract: Objective: Joint injury involving destabilisation of the joint and damage to the articular cartilage (e.g., sports-related injury) can result in accelerated post-traumatic osteoarthritis (PTOA). Destabilised medial meniscotibial ligament (DMM) surgery is one of the most commonly used murine models and whilst it recapitulates Osteoarthritis (OA) pathology, it does not necessarily result in multi-tissue injury, as occurs in PTOA. We hypothesised that simultaneous cartilage damage and joint destabilisation would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Using an intra-articular fracture model, obesity increased synovial inflammation. 10 Although synovitis and inflammation can occur in association with an initial DMM surgery, DMM can have differential effects on joint inflammation, as demonstrated by two reports, one showing low-level synovitis following DMM 33 while another did not find differences in synovitis. 34 Obesity increases synovial thickness and synovial inflammation in DMM.…”
Section: Discussionmentioning
confidence: 99%
“…Using an intra-articular fracture model, obesity increased synovial inflammation. 10 Although synovitis and inflammation can occur in association with an initial DMM surgery, DMM can have differential effects on joint inflammation, as demonstrated by two reports, one showing low-level synovitis following DMM 33 while another did not find differences in synovitis. 34 Obesity increases synovial thickness and synovial inflammation in DMM.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was previously shown that the development of histologic OA following DMM in mice is associated with poor functional outcomes including pain 58 , 59 . The data presented in this study demonstrate that the collagen–OSCAR interaction contributes to cartilage and joint degeneration following DMM, and consistent with prior works 58 , 59 . Such pathologic changes are expected to result in pain and impaired motile function.…”
Section: Discussionmentioning
confidence: 99%
“…While histopathology rather than imaging remains the gold standard for measuring OA structural disease onset and progression in pre-clinical animal models, as in patients emphasis has shifted to a more global evaluation of joint-wide pathology facilitated in part by use of smaller species such as mice 19,21,22 . To date however, there has been limited investigation in pre-clinical models of the joint-tissue pathology associations observed in patients 23,24 , and none that we are aware of…”
Section: Osteoarthritis Andcartilagementioning
confidence: 99%